Toward an enhanced policy and action framework to address energy poverty in the Iberian Peninsula: An exploratory analysis - Roberto Barrella; Pedro Palma; João Pedro Gouveia; José Carlos Romero; Eva Arenas; José Ignacio Linares (Heliyon)
Portugal and Spain share a historical and territorial bond and a severe challenge to alleviate energy poverty, a complex issue affecting millions of people. Reducing this social scourge is a major concern for both governments, which have published national energy poverty strategies in recent years.This paper critically explores the Iberian policy frameworks to provide insights into prioritising and enhancing energy poverty actions. This comparative analysis focuses on national plans’ and critically evaluates the existing and planned policy measures. Additionally, it analyses the potential stakeholder networks that might contribute to mitigating energy poverty.Findings show good practices to be fostered but shortcomings in policy reach and the impact of some programs. An automatic cash transfer covering all necessitated energy services might be a valid solution for both countries to mitigate energy vulnerability in the short run. In the medium-long term, an ad hoc, easy-to-apply-to, energy efficiency subsidy program might boost the structural improvement of vulnerable households’ well-being and financial situations. On the planning side, the Iberian national energy poverty strategies have been grounded on similar key action pillars, but their policy proposals lack detailed funding estimates and associated time frames, and do not include ex-ante impact evaluations. These countries can benefit from cross-exchange of good practices and, with the help of the identified stakeholders, reinforce the implementation of their energy poverty policy plans.The policy recommendations and identified strengths and weaknesses presented in this paper are informative for Iberian decision-makers and other EU Member States, contributing insights on how to enhance and prioritise energy poverty actions.